Linkages between Bio-Resources and Human Livelihood: A Case Study of Adi Tribes of Mirem Village, Arunachal Pradesh (India) - Nimachow, Gibji; Taga, Tahong; Tag, Hui; Dai, Oyi (The Initiation, 2010)
The living of man in all societies is largely guided by the availability or otherwise of natural bio-resources. However, the tribal people who are regarded as in the primitive stage and experiencing slow pace of development have a high degree of dependence on the natural resources for their livelihood. Bio - resources consist of all biotic components of environment, which have utility and function in satisfying the individual wants as well as social wants of man. Recently, the importance of the study on man and nature relationship has gained momentum globally and has emerged as main concern for both the developed and developing nations worldwide. As such, the tribal dominated areas by virtue of having the higher percentage of forest cover have become prime area for research in the world context for sustainable use of bio-resources. The State of Forest Report, 2003 has placed Arunachal Pradesh second after Mizoram in terms of forest coverage with 68, 019 sq. km. under forest cover. An analysis of the linkages between the bio - resources and human livelihoods may prove significant and helpful in attaining the first rank in the total coverage of forests in the country. The Adi tribe is a major tribal group of Arunachal Pradesh who mostly inhabit East, West and Upper Siang districts. An assessment of linkages of human livelihood and the bioresources in the Adi inhabited area proved to be helpful in the sustainable management of natural resources. A household survey with the help of suitable structured questionnaire was conducted for Mirem village. Personal interview with the village elders was an important tool for the final analysis. The study finds that these people are forest lovers and they are strongly abated with their existing forests. The traditional folk tales, festivities and myths are strongly linked with nature and deeply influenced by the forest ecology and environment. Economic activities, material culture, food habits, house-building materials, ritual performances and herbal medicine all are collected from the forests. The study found that these people are highly dependent on the bio-resources for their livelihood even in this age of scientific and technological development. Key Words: Bio-resources, livelihood, Adi tribes, Man-nature relationship, Sustainable natural resources management, Forest cover, Material culture, Herbal medicine. DOI: 10.3126/init.v2i1.2542 The Initiation Vol.2(1) 2008 pp183-198